2023
DOI: 10.1371/journal.pone.0283347
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bread wheat (Triticum aestivum L.) genotypes for drought tolerance using morpho-physiological traits under drought-stressed and well-watered conditions

Abstract: Increasing frequency of drought spells occasioned by changing climatic conditions, coupled with rise in demand for bread wheat, calls for the development of high yielding drought resilient genotypes to enhance bread wheat production in areas with moisture deficit. This study was designed to identify and select drought-tolerant bread wheat genotypes using morpho-physiological traits. One hundred and ninety-six bread wheat genotypes were evaluated in greenhouse and field experiments, under well-watered (80% of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 70 publications
1
1
0
Order By: Relevance
“…Yield, the paramount economic characteristic of wheat, and its grain production serve as the primary criteria for drought tolerance. In this study, a significant reduction was observed in yield attributes due to water stress in both wheat cultivars, with Sakha 95 experiencing a lesser decrease, matching with other studies [ 119 , 120 ]. The decrease in wheat yield due to water stress can be linked to drought’s inhibitory impact on plant growth, stemming from the suppression of various metabolic processes.…”
Section: Discussionsupporting
confidence: 91%
“…Yield, the paramount economic characteristic of wheat, and its grain production serve as the primary criteria for drought tolerance. In this study, a significant reduction was observed in yield attributes due to water stress in both wheat cultivars, with Sakha 95 experiencing a lesser decrease, matching with other studies [ 119 , 120 ]. The decrease in wheat yield due to water stress can be linked to drought’s inhibitory impact on plant growth, stemming from the suppression of various metabolic processes.…”
Section: Discussionsupporting
confidence: 91%
“…Under drought stress, wheat plants notably change their aboveground traits (Figure 2), encompassing plant height, coleoptile length, leaf size, shape and perimeter, leaf surface morphology and waxiness, and various anatomical adjustments [80][81][82][83]. These variations are contingent upon the drought susceptibility of the genotypes, the duration and severity of drought events, as well as the growth stage of the plants [18,73,84,85].…”
Section: Aboveground Traitsmentioning
confidence: 99%
“…Utilizing these simple belowground and aboveground traits as selection criteria for drought tolerance holds promise for supporting breeding efforts aimed at developing drought-resistant wheat genotypes [56,[81][82][83]90]. By focusing on these traits, breeders can effectively identify and select genotypes that are more likely to withstand water scarcity; however, to achieve optimal results, it is important to conduct comprehensive research that considers not only the individual traits but also their interactions with one another.…”
Section: Aboveground Traitsmentioning
confidence: 99%
“…There is also a reduction in leaf area, which is associated with reduced assimilate availability [34,35]. In wheat, Sewore et al [36] found that there was significant leaf rolling in response to water deficit. A similar phenomenon has been observed in maize.…”
Section: Introductionmentioning
confidence: 99%